2021
DOI: 10.1101/2021.09.25.21264111
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemiology, Clinico-Pathological Characteristics, and Comorbidities of SARS-CoV-2 infected Pakistani Patients

Abstract: SARS-CoV-2 is a causative agent for COVI-19 disease, initially reported from Wuhan, China. Infected Patients experienced mild to severe symptoms, resulting in several fatalities due to a weak understanding of its pathogenesis, which is the same even to date. This cross-sectional study has been designed on four hundred and fifty-two symptomatic, mild-to-moderate, and severe/critical patients to understand the epidemiology and clinical characteristics of COVID-19 patients with their comorbidities and response t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…Diagnosed Covid-19 infected cases of 452 patients including 279 males and 173 females with their age ranged between 44 and 72 years, admitted to five leading hospitals in different cities of the Pakistan, were included in the study conducted by Saadia Omer et al [14]. They reported that these patients were suffering from fever, followed by cough, dyspnea, fatigue, myalgias, generalized body aches, vomiting, headache, diarrhea, sore throat, sputum, production, nausea, loss of taste, rhinorrhea, anosmia and nasal congestion.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosed Covid-19 infected cases of 452 patients including 279 males and 173 females with their age ranged between 44 and 72 years, admitted to five leading hospitals in different cities of the Pakistan, were included in the study conducted by Saadia Omer et al [14]. They reported that these patients were suffering from fever, followed by cough, dyspnea, fatigue, myalgias, generalized body aches, vomiting, headache, diarrhea, sore throat, sputum, production, nausea, loss of taste, rhinorrhea, anosmia and nasal congestion.…”
Section: Discussionmentioning
confidence: 99%